STRUKTUR POPULASI DAN MASA REPRODUKSI UDANG REGANG - DAISY WOWOR (BERITA BIOLOGI, 1985)
DAISY WOWOR. 1985. Population structure and spawning period of Udang Regang (Macrobrachium sintangense). BeritaBiologi 3(3): 116- 120. Population structure and spawning period of Macrobrachium sintangense was observed in a coast of a small artificial lake, Situ Ciletuh, Ci gombong, West Java, from December 1981 to August 1982. Examination of the class-size frequency indicated the growth rate of body length of the population, and its spawning periods.The mean growth rate of carapace was 3.44 mm per month.Sex ratio was 1:1, significant at the 95% level. The number of the larger males is greater than the females, which indicate the phenomenon of sexual dimorphism.This is due to the differences of growth and the maximum body size attained by the males and females. It was observed that M. sintangense spawns throughout the year, maximum spawning activity occurs between March and June.